Pengangkatan anak kewenangan pengadilan agama - Sy., Musthofa, 1969-; Indonesia (Rawamangun, Jakarta : Kencana Prenada Media Group, 2008)
On child adoption and its procedures according to Indonesian and Islamic laws
Includes the text of : Undang-Undang Tentang Perubahan Atas Undang-Undang nomor 7 tahun 1989 Tentang Peradilan Agama
Includes bibliographical references (p. [283]-289)
Keywords: Adoption -- Law and legislation -- Indonesia